2015
DOI: 10.1007/s40520-015-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease (PD) with dementia and falls is improved by AChEI? A preliminary study report

Abstract: We hypothesize that AchEI could improve stability, balance and postural instability in addition to cognitive performance in PD with MCI and balance deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Therefore, the effect of carvacrol on memory improvement could be due to its anticholinesterase activity and modulation of the cholinergic system. In agreement with this, it has been reported that acetylcholinesterase inhibitors have a beneficial effect on cognitive performance in PD 36 .…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the effect of carvacrol on memory improvement could be due to its anticholinesterase activity and modulation of the cholinergic system. In agreement with this, it has been reported that acetylcholinesterase inhibitors have a beneficial effect on cognitive performance in PD 36 .…”
Section: Discussionsupporting
confidence: 84%
“…OM of gait may have a future role in the assessment of PD as there is evidence that some interventions may improve gait stability and balance. 14 , 15 OM of gait parameters can already, in some specific situations, influence PD management decisions. 15 , 16 If effective treatment is developed for any of these PD symptoms, they may become useful targets for OM.…”
Section: What Should Be Measured In Pd?mentioning
confidence: 99%
“…1 Postural control is severely reduced in PD and postural instability is thought to be one of the main symptoms of the disease. [2][3][4] Walking speed is reduced in PD patients and this is accompanied by a decrease in arm swing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is an increase in cadence, double support, and left-right gait asymmetry and there is a decrease in bilateral coordination. 1 Gait disorders and postural instability increase the risk of falls in PD, which causes severe head trauma, fractures and mortality. 1 In addition, levodopa-induced dyskinesia, symptomatic orthostatic hypotension, sudden loss of postural reflexes, coexisting neurological or other medical disorders, and environmental factors are the other risk factors for falls in PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation